Infrastructure project financing through sukuk as an alternative to conventional bond financing - Mohd Sadad, Mahmud; Ibraheem Alani, AbdulKareem (2019)
The infrastructure development is one of the vital elements in achieving the goals of the country development. When infrastructure and other public facilities are available, basic human needs can be met accurately. Financing infrastructure has been the main concern of many countries and there is a very little foreign direct investment in developing nations for many reasons. These nations apply for loans from international institutions which are expensive with many attached conditions. Similarly, evidence have shown from Gulf Cooperation Council (GCC) and Malaysia that the adoption of sukuk is an assured way toward infrastructural development of a country. For this reason, many authors perceived sukuk as alternative to conventional bond for infrastructure projects and other essential needs for countries to develop. Therefore, this study is motivated by the infrastructural development which has taken place in those countries that have been practising/using sukuk as tool for infrastructure development. This innovation will increase a lot of strategic advantage and economic development of countries by utilizing sukuk as an alternative source of funding. Using sukuk as infrastructural development’s tool will also assist countries that find it difficult to fulfil the requirement for the conventional bond.